Philosophical Foundations And Its Relation With Education - Samuel Aloysius Ekanem (dialektika kontemporer, 2021)
The foundations of the curriculum are the values, traditions, factors, and forces that influence the kind, quantity, and quality of experiences the school offers its learners. The curriculum has many influential forces which have engendered a tremendous impact upon the construction of the curriculum. In other words, philosophical foundations are those elements of philosophy which have a bearing on choices made with regard to the purposes and contents of the school. It is in the area of curriculum planning that philosophy in education reflects itself. The goals or objectives of any educational effort can only be implemented through a curriculum that translates them into subjects, units of instruction, themes, or topics that enter the classroom. They are to be reflected in the reading, the instruction, and the activities of the pupils under the guidance and direction of the teachers. For understanding the concept of philosophical foundations, there is a need to know the relationship between philosophy and education. In this work, I will be reviewing three philosophical foundations: idealism, naturalism, and pragmatism, and their relationship with education.